The species composition and density of earthwarms in some landscapes in the Northern Vietnam - Thanh Binh, Tran Thi; Ha, Nguyen Thi (Academia Journal of Biology, 2015)
The species composition and density of earthworms were studied by analyzing earrthwarms collected in July and December from different landscapes: hilly area (Luc Ngan, Bac Giang), high plain (Yen Dung, Bac Giang), low plain (Tien Du, Bac Ninh and Quynh Phu, Thai Binh) and coastal plain (Hai Hau, Nam Dinh). Of the total 50 species recorded the most species were collected in Luc Ngan (33 species, 8 genera, 6 families), followed by Yen Dung (24 species, 4 genera, 4 families); Tien Du (14 species, 3 genera, 3 families); Quynh Phụ (14 species, 4 genera, 4 families) and Hai Hau (11 species, 1 family, 1 genus). Thus, species composition and diversity of earthworms descend from the hilly area to the high plain, low plain and the coastal plain. Species composition of earthworms in Luc Ngan hilly area showed the highest similarity (42.11%) with that of Yen Dung followed by Tien Du and Quynh Phu (34.04%) and Hai Hau (22.73%). Most species (50% of species) have the density lower than 0.3 individual/m2. The density of earthworms is highest in the plain areas, lower in Luc Ngan hilly area, and lowest in the Hai Hau coastal plain.